الاستفادة من التقنيات الحديثة لطباعة الأقمشة واستخدامها كخامة في تنفيذ وحدات الأثاث الخشبي المعاصر والمستلهم من الزخارف الخطية الإسلامية: تطبيقا على وحدة أثاث خشبي - عبدالمتولي، محمود محمد الشحات; حسين، رشا رجب إبراهيم (الجمعية العربية للحضارة والفنون الإسلامية, 2022)
تعتبر الأقمشة من الخامات الهامة في كثير من المجالات خاصة مجال التصميم الداخلي والأثاث واستخدامها كخامة ضرورية وأساسية في الكثير من المجالات والأنشطة سواء كانت في المفروشات أو المعلقات وغيرها......، والتي بدورها تعطي طابع الثراء والرقى في هذا المجال وتقوم بإرساء وظائف هامة وضرورية لا غنى عنها سواء استخدمت كمفروشات أو ستائر أو معلقات أو كعنصر مكمل لوحدات الأثاث مما يعرضها للكثير من عوامل التلف المباشر سواء كانت عوامل بيئية أو عوامل فيزيائية أو سوء استخدام ومن هنا جاءت فكرة البحث في كيفية معالجة الأقمشة ووحدات الأثاث من خلال استخدام تقنيات تكنولوجية حديثة يتم تنفيذها بطرق علمية مستحدثة لحمايتها من عوامل التلف وظهر الاهتمام واضحا بأهمية التكنولوجيا وارتباطها بالتصميم والتنفيذ، حيث تنبه المتخصصون والباحثون إلى الاستفادة من التقنيات الحديثة لطباعة المنسوجات للحصول على أشكال لا نهائية من التصميمات ذات التفرد والتميز والتنوع بما يزيد من جودة المنتج وقد باتت مركبات من المواد الحديثة في مجال طباعة وتجهيز المنسوجات بما لها من خواص عالية الجودة مثل اللمعان والمطاطية والثبات على كافة الألياف النسيجية وسوف يتم استخدام متراكبات مختلفة في تجهيز المنسوجات الأقمشة وطباعة التصميم بأحبار السيليكون ذاتها. ومن ثم يمكن الاستفادة من هذه النوعية من الأقمشة المعالجة والمستوحى تصميمها من الزخارف الإسلامية بشكل معاصر كخامه تستخدم في تنفيذ قطع الأثاث الخشبي ذات الطابع الإسلامي المعاصر والمستوحى من الزخارف الخطية الإسلامية لإعطائها شكل جمالي لتحقيق اتصال بصري ذات قيمة جمالية معاصرة بهوية إسلامية. وللحفاظ على الهوية الإسلامية بشكل معاصر تم استلهام الفكر التصميمي للأقمشة ووحدات الأثاث من الزخارف الإسلامية بصورة معاصرة تطبيقا على وحدة أثاث خشبي. ومع التطور الهائل في مجال التصميم بعناصره المختلفة من استراتيجيات ابتكارية إبداعية وتقنيات حديثة في التنفيذ والإنتاج إلا أن التشكيل بالكتابة العربية وما تمتلكه من تفرد خاص بالمجتمع العربي لم يحظ اهتماما من قبل المصممين. Fabrics are important materials in many areas, especially interior design and furniture and use as a necessary and essential raw material in many areas and activities, whether in furnishings, suspensions, etc. Which in turn gives the character of richness and sophistication in this area and establishes important and necessary functions indispensable whether used as furnishings, curtains or suspensions or as a complement to furniture units, which exposes them to many factors of direct damage, whether environmental or factors Physical or misuse Hence the idea of researching how to process fabrics and furniture units through the use of modern technological techniques implemented in scientific ways developed to protect them from damage factors and the interest in the importance of technology and its association with design and implementation, where it warns specialists and researchers to take advantage of modern technologies to print textiles to obtain infinite forms of designs uniqueness, excellence and diversity to increase the quality of the product and have become vehicles of Modern materials in the field of printing and processing textiles with their high quality properties such as gloss, rubber and stability on all textile fibers will be used different overlaps in the processing of textile fabrics and printing the design with silicon inks themselves. This type of processed fabrics, inspired by Islamic decorations, can therefore be used in a contemporary manner, such as ore, used in the implementation of contemporary Islamic wooden furniture pieces inspired by linear decorations. Islamic to give it an aesthetic form to achieve a visual connection of contemporary aesthetic value to an Islamic identity. To preserve the Islamic identity in a contemporary way, the design thought of fabrics and furniture units was inspired by contemporary Islamic decorations in accordance with a wooden furniture unit. With the tremendous development in the field of design with its various elements of innovative creative strategies and modern techniques in implementation and production, the composition of Arabic writing and its uniqueness in the Arab society did not receive attention from designers.
Keywords: فنون الطباعة -- الزخارف الإسلامية -- الأثاث الخشبي -- التراث المعماري